2013
DOI: 10.4018/ijeoe.2013100102
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Nonlinear Dynamic Systems with Volterra Polynomials

Abstract: The paper presents a review of the studies that were conducted at Energy Systems Institute (ESI) SB RAS in the field of mathematical modeling of nonlinear input-output dynamic systems with Volterra polynomials. The first part presents an original approach to identification of the Volterra kernels. The approach is based on setting special multi-parameter families of piecewise constant test input signals. It also includes a description of the respective software; presents illustrative calculations on the example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
(48 reference statements)
0
10
0
3
Order By: Relevance
“…The identification of the mesh analogs of Volterra kernels tuned to test signals with amplitudes of 25% of the initial values of D 0 = 0.16 kg/s, Q 0 = 100 kW was carried out using the technique [42,44] for T = 40 s, h = 1 s. Figure 3 shows mesh analogs for K 1 , K 2 , K 11 characterizing the influence of ∆D(t) and ∆Q(t) on the change of ∆i(t). Kernels were identified on the discrete mesh with the step h = 1 using responses ∆i(t) to test signals of the form Equation ( 5) with amplitudes equal to 25% of the initial values.…”
Section: Computational Experiments Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The identification of the mesh analogs of Volterra kernels tuned to test signals with amplitudes of 25% of the initial values of D 0 = 0.16 kg/s, Q 0 = 100 kW was carried out using the technique [42,44] for T = 40 s, h = 1 s. Figure 3 shows mesh analogs for K 1 , K 2 , K 11 characterizing the influence of ∆D(t) and ∆Q(t) on the change of ∆i(t). Kernels were identified on the discrete mesh with the step h = 1 using responses ∆i(t) to test signals of the form Equation ( 5) with amplitudes equal to 25% of the initial values.…”
Section: Computational Experiments Resultsmentioning
confidence: 99%
“…The technique of using scalar input signals in Equation ( 5) is described in detail in the review [42] (see the section "About one approach to identification of Volterra kernels"). For the case of a signal represented as a vector function of time, the series of articles [36,39,[42][43][44] presents algorithms for choosing the amplitudes of test signals for identifying Volterra kernels, which, in general, can be represented as follows:…”
Section: Volterra Equations Of the First Kind With Two Variable Integ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the Volterra polynomials in thermal power engineering was demonstrated in [10] for solving the problem of creating a method for the dynamic calculation of boiler units. And in [11,12], using the example of a heat exchanger model with independent heat supply, represented as an object with lumped parameters, the authors showed that an integral model based on a quadratic segment of the Volterra series can be employed to fairly accurately and quickly describe nonlinear transient processes in the heat exchanger. A detailed description of this object is presented in [13].…”
Section: Introductionmentioning
confidence: 99%